Share capital in the Polish simple joint-stock company in light of the existing law and proposed European legislation - Jarosz, Iwo (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In recent years we have witnessed an almost unprecedented effort of legislators and legal academics in Europe to make limited liability companies in various jurisdictions more modern, simpler and more accessible. These endeavors are usually related to the liberalization of statutory requirements regarding the minimum share capital amounts. Lively debates among academics and practitioners, as well as regulatory competition, seem to be the factors making the legislative changes dynamic and evolutionary. The issue of limited liability companies’ regulatory reform were also the subject of proposed European legislation, including the now abandoned proposal of a harmonised single-member limited liability company model known as Societas Unius Personae SUP. In Poland there has also been, for almost a decade, a discussion on whether and how to follow the example of Germany and its Unternehmergesellschaft and other European countries and liberalize the capital requirements for the Polish limited liability company. Lately the Polish legislator has introduced the so-called simple joint-stock company prosta spółka akcyjna, which had been drafted to be an attractive offer for start-ups, aiming, in the perception of its proponents, to achieve the modernization and simplification desired by contemporary legislators and supposedly accomplished in other jurisdictions, all the while maintaining serious levels of creditor protection. The author employs formal-dogmatic and comparative methods to describe the capital structure of the new company type and to confront it with certain other statutory developments, especially the Societas Unius Personae as a serious and well-thought-out, nonetheless failed venture, to try to assess the solutions set forth by the Polish legislator.
Keywords: company; limited liability; share; capital; simple joint stock company; Societas Unius Personae